Prognostic significance of nutritional markers in metastatic gastric and esophageal adenocarcinoma. (9th December 2020) - Ma, Lucy X.; Taylor, Kirsty; Espin‐Garcia, Osvaldo; Anconina, Reut; Suzuki, Chihiro; Allen, Michael J.; Honorio, Marta; Bach, Yvonne; Allison, Frances; Chen, Eric X.; Brar, Savtaj; Swallow, Carol J.; et al.
Abstract: Background: Malnutrition and sarcopenia are poor prognostic factors in many cancers. Studies in gastric and esophageal (GE) cancer have focused on curative intent patients. This study aims to evaluate the prognostic utility of malnutrition and sarcopenia in de novo metastatic GE adenocarcinoma. Methods: Patients with de novo metastatic GE adenocarcinoma seen at the Princess Margaret Cancer Centre from 2010 to 2016 with an available pre‐treatment abdominal computed tomography (CT) were included. Malnutrition was defined as nutritional risk index (NRI) <97.5. Skeletal muscle index (SMI) was measured at the L3 level (sarcopenia defined as SMI <34.4 cm 2 /m 2 in women and <45.4 cm 2 /m 2 in men). Patients receiving chemotherapy had NRI and SMI recalculated at the time of first restaging CT. Results: Of 175 consecutive patients, 33% were malnourished and 39% were sarcopenic at baseline. Patients with pretreatment malnourishment had significantly shorter overall survival (OS; 5.8 vs. 10.9 months, p = 0.000475). Patients who became malnourished during chemotherapy had worse OS compared to those who maintained their nutrition (12.2 vs. 17.5 months p = 0.0484). On univariable analysis, ECOG ( p < 0.001), number of metastatic sites ( p = 0.029) and NRI ( p < 0.001) were significant prognostic factors while BMI ( p = 0.57) and sarcopenia ( p = 0.19) were not. On multivariable analysis, ECOG ( p < 0.001), baseline NRI ( p = 0.025), and change in NRI during treatment ( p < 0.001) were significant poor prognostic factors for OS. Conclusions: In de novo metastatic GE adenocarcinoma patients, ECOG, pretreatment NRI and change in NRI were significant prognostic factors for OS while sarcopenia was not. Use of NRI at baseline and during treatment can provide useful prognostic information. Abstract : In de novo metastatic gastric and esophageal adenocarcinoma patients, ECOG, pre‐treatment nutritional risk index (NRI) and change in NRI during treatment were significant prognostic factors for overall survival while sarcopenia was not. Use of NRI at baseline and during treatment can provide useful prognostic information.